THE EFFECT OF TELEMONITORING ON DIABETES DISTRESS IN PATIENTS WITH TYPE II DIABETES MELLITUS IN RI-RDTL BORDER REGION - Sanan, Yane Cristiana Ua; Nitsae, Veronika (Jurnal Keperawatan, 2025)
Diabetes mellitus (DM) is associated with various complications, one of which is diabetes distress. Although numerous technology-based interventions have been implemented for patients with DM the impact of these interventions on diabetes distress remains inadequately understood. This study aimed to assess the effect of telemonitoring on diabetes distress among patients with type II DM in border regions. A quasi-experimental pre and post-test research design, without a control group, was utilized for the study. Conducted from July to September 2024, at the Puskesmas in the Belu Regency, the study involved a total sample of 22 respondents, selected through consecutive sampling. The Indonesian version of the Diabetes Distress 17 (DDS17) was used to measure diabetes distress. The telemonitoring intervention consisted of telephone calls lasting approximately 15-20 minutes. Data analysis was performed using the Wilcoxon signed-rank test. Results indicated that the mean value of diabetes distress before the intervention was 2.82, which decreased to 1.86 after the intervention. The difference in the decrease in the average value before and after the intervention was 0.96. Statistical analysis using the Wilcoxon signed rank test revealed a p-value of less than 0.05, indicating a significant difference in diabetes distress before and after the telemonitoring intervention. Therefore, telemonitoring can be considered a viable technology-based intervention through telephone calls to reduce distress in DM patients, particularly in border areas.